Contraception in Adolescents - Raidoo, Shandhini; Pearlman Shapiro, Marit; Kaneshiro, Bliss (Seminars in Reproductive Medicine, 2021)
Adolescents are at risk for unwanted pregnancy when they become sexually active, and contraception is an important part of mitigating this risk. Use of contraceptive methods, and long-acting reversible contraceptive methods such as implants and intrauterine devices in particular, has increased among adolescents. Although sexual activity has declined and contraceptive use has increased among adolescents in the United States in recent years, the unintended pregnancy rate remains high. All of the currently available contraceptive methods are safe and effective for adolescents to use; however, adolescents may have specific concerns about side effect profiles and unscheduled bleeding that should be addressed during contraceptive counseling. Healthcare providers should prioritize adolescents' needs and preferences when approaching contraceptive counseling, and also consider the unique access and confidentiality issues that adolescents face when accessing contraception.
Keywords: adolescents; contraception; pregnancy; birth control